Hubungan tingkat kecemasan dengan kualitas tidur pada lansia - Utami, Endang Sri; Suratini, Suratini; Isnaeni, Yuli (JOURNAL OF Community Health Issues, 2024)
Background: Sleep disturbance is a common problem in the elderly and can be influenced by psychological factors such as anxiety. Poor sleep quality in the elderly has an impact on functional, physical, mental and social decline. Purpose: This study aims to determine the relationship between anxiety levels and sleep quality in the elderly at the panuntun elderly posyandu Kwarasan Nogotirto Gamping Sleman. Method: This study used quantitative methods with descriptive correlation design and cross-sectional approach. The sample was 70 elderly people selected by total sampling technique. The instruments used were the Hamilton Anxiety Rating Scale (HARS) questionnaire to measure anxiety levels and the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. Data analysis using Kendall's Tau test_b Results: The results showed that most respondents experienced anxiety in the moderate category as many as 43 respondents (61.4%) and had poor sleep quality as many as 45 respondents (64.3%). The results of Kendall's Tau_b test showed that there was no significant relationship between anxiety levels and sleep quality in the elderly with a p-value of 0.961 (p> 0.05) and a correlation coefficient of -0.006. Conclusion: There is no significant relationship between anxiety levels and sleep quality in the elderly. This shows that sleep quality in the elderly is more influenced by other factors such as physical condition, comorbidities, environment, and other psychosocial factors. Keywords: Anxiety, Sleep Quality, Elderly. Pendahuluan: Gangguan tidur merupakan masalah umum pada lansia dan dapat dipengaruhi oleh faktor psikologis seperti kecemasan. Kualitas tidur yang buruk pada lansia berdampak pada penurunan fungsi, fisik, mental dan sosial. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan tingkat kecemasan dengan kualitas tidur pada lansia di Posyandu Lansia Panuntun Kwarasan Nogotirto Gamping Sleman. Metode: Penelitian ini menggunakan metode kuantitatif dengan desain deskriptif korelasi dan pendekatan cross-sectional. Sampel sebanyak 70 lansia yang dipilih dengan teknik total sampling. Instrumen yang digunakan adalah kuesioner Hamilton Anxiety Rating Scale (HARS) untuk mengukur tingkat kecemasan dan Pittsburgh Sleep Quality Index (PSQI) untuk mengukur kualitas tidur. Analisis data menggunakan uji Kendall’s Tau_b Hasil: Hasil penelitian menunjukkan sebagian besar responden mengalami kecemasan pada kategori sedang sebanyak 43 responden (61,4%) dan memiliki kualitas tidur cukup buruk sebanyak 45 responden (64,3%). Hasil uji Kendall’s Tau_b menunjukkan tidak terdapat hubungan yang signifikan antara tingkat kecemasan dengan kualitas tidur pada lansia dengan nilai p-value sebesar 0,961 (p > 0,05) dan nilai koefisien korelasi sebesar -0,006. Simpulan: Tidak terdapat hubungan yang signifikan antara tingkat kecemasan dengan kualitas tidur pada lansia. Hal ini menunjukkan bahwa kualitas tidur pada lansia lebih dipengaruhi oleh faktor lain seperti kondisi fisik, penyakit penyerta, lingkungan, dan faktor psikososial lainnya. Kata Kunci : Kecemasan, Kualitas Tidur, Lansia